The Effect of Commercial Feeding with Different Brands on Physical Quality Kampung Unggul Balitbangtan (Kub) Chicken Meat - Gayuh Syaikhullah; Himmatul Khasanah; Nur Muhamad; Aan Awaludin; Satria Budi Kusuma (Universitas Andalas, 2024)
The purpose of this study is to ascertain how giving commercial feed of various brands affects the physical quality of meat obtained from Kampung Unggul Balitbangtan (KUB) chickens on pH values, cooking losses and water holding capacity. The Completely Randomized Design (RAL) and Analysis of Variance (ANOVA) techniques were used in this study. The Duncan Multiple Range Test (DMRT) was used to see if there were any notable changes. This research used 160 Day Old Chicks (DOC) with 4 commercial feed treatments with different brands, namely P1 (WK Feed). P2 (CPH Feed), P3 (PAT Feed) and P4 (CFD Feed) with level of protein contains each brand. The results of this study show that giving commercial feed with different brands can have a significant effect (P